2020
DOI: 10.1186/s12864-020-07152-2
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide study of pineapple (Ananas comosus L.) bHLH transcription factors indicates that cryptochrome-interacting bHLH2 (AcCIB2) participates in flowering time regulation and abiotic stress response

Abstract: Background Transcription factors (TFs) are essential regulators of growth and development in eukaryotes. Basic-helix-loop-helix (bHLHs) is one of the most significant TFs families involved in several critical regulatory functions. Cryptochrome-interacting bHLH (CIB) and cryptochromes form an extensive regulatory network to mediate a plethora of pathways. Although bHLHs regulate critical biological processes in plants, the information about pineapple bHLHs remains unexplored. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 53 publications
(88 reference statements)
0
13
0
Order By: Relevance
“…Since the transcriptome data are not comprehensive in this study, and the genome of A. argyi has not been published, some bHLH family were still might not be identified yet. Based on genome data, 147 bHLH genes in Arabidopsis thaliana ( Toledo-Ortiz et al, 2003 ), 121 bHLH genes in pineapple ( Aslam M. et al, 2020 ) and 174 bHLH genes in sorghum ( Fan et al, 2021 ) were identified. Therefore, the identification of bHLH family members needs to be improved by genomic data.…”
Section: Discussionmentioning
confidence: 99%
“…Since the transcriptome data are not comprehensive in this study, and the genome of A. argyi has not been published, some bHLH family were still might not be identified yet. Based on genome data, 147 bHLH genes in Arabidopsis thaliana ( Toledo-Ortiz et al, 2003 ), 121 bHLH genes in pineapple ( Aslam M. et al, 2020 ) and 174 bHLH genes in sorghum ( Fan et al, 2021 ) were identified. Therefore, the identification of bHLH family members needs to be improved by genomic data.…”
Section: Discussionmentioning
confidence: 99%
“…The bHLH family has been widely identified in many plants, including Brassica rapa ssp. pekinensis [ 11 ], Solanum lycopersicum [ 12 ], common bean [ 13 ], Malus pumila [ 14 ], Arachis hypogaea [ 15 ], Brachypodium distachyon [ 16 ], Zea mays [ 17 ], Triticum aestivum [ 18 ], Phyllostachys edulis [ 19 ], Carthamus tinctorius [ 20 ], Chinese jujube [ 21 ], Piper nigrum [ 22 ], Jilin ginseng [ 23 ], Ananas comosus [ 24 ], Fagopyrum tataricum [ 25 ], and sorghum [ 26 ]. The bHLH genes have been conserved in the evolutionary history of the plant kingdom.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, bHLH and MADS-box gene family members play a key role in plant reproductive development. For example, a previous study showed the early flowering phenotype in the Arabidopsis cib2 mutant and the complementation of the early flowering phenotype by 35S::AcCIB2 -GFP [ 58 ]. The ectopic overexpression of one Phyllostachys edulis MADS-box gene, PeMADS5 , triggered earlier flowering in Arabidopsis and the development of an aberrant flower phenotype [ 59 ].…”
Section: Discussionmentioning
confidence: 99%